1998
DOI: 10.1046/j.1365-2141.1998.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic arsenic poisoning associated with treatment of acute promyelocytic leukaemia

Abstract: Summary. Seven relapsed and/or refractory acute promyelocytic leukaemia patients were treated by arsenic trioxide (As 2 O 3 ). Four patients (4/7, 57%) achieved complete remission after one to three cycles of treatment and the most common acute side-effect was fluid retention (in six patients, 86%), including weight gains and pleuro-pericardial effusions. Evident polyneuropathy compatible with chronic arsenic toxicity was noted in two of the three patients who received As 2 O 3 maintenance therapy and one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 9 publications
1
63
0
2
Order By: Relevance
“…In addition, it was reported that As 2 O 3 at a dose of 10 mg/day could cause severe toxic effect, particularly in the treatment of de novo cases, leading to liver function failure. Huang et al 11 reported severe acute sideeffects including pleural effusion (5/7), pericardial effusion (4/7), and some chronic arsenic toxicity. We conducted this study for the purpose of investigating the clinical efficacy of low-dose As 2 O 3 and its possible reduction of side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that As 2 O 3 at a dose of 10 mg/day could cause severe toxic effect, particularly in the treatment of de novo cases, leading to liver function failure. Huang et al 11 reported severe acute sideeffects including pleural effusion (5/7), pericardial effusion (4/7), and some chronic arsenic toxicity. We conducted this study for the purpose of investigating the clinical efficacy of low-dose As 2 O 3 and its possible reduction of side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…14 In contrast to its apparent curative effects, As 2 O 3 is known to be a carcinogen in human organs, such as skin and lung, and it has serious side effects such as fluid retention in patients. 15 Other chronic side effects include polyneuropathy, palmar keratosis and skin hyperpigmentation. 15 It is, therefore, desirable to develop other drugs that act by a similar mechanism to that of As 2 O 3 but lack the side effect.…”
mentioning
confidence: 99%
“…15 Other chronic side effects include polyneuropathy, palmar keratosis and skin hyperpigmentation. 15 It is, therefore, desirable to develop other drugs that act by a similar mechanism to that of As 2 O 3 but lack the side effect. While the mechanism of the induction of apoptosis in tumor cells by As 2 O 3 is not well understood, As 2 O 3 has been used to mimic the effects of heat shock on cells.…”
mentioning
confidence: 99%
“…4 The most frequent acute adverse effects of treatment of APL with As 2 O 3 reported so far seem to be fluid retention, cardiac and hepatic toxicity as well as gastrointestinal and dermatological symptoms. Polyneuropathy and muscular atrophy were noted as chronic side-effects.…”
Section: Figurementioning
confidence: 99%
“…After prolonged administration of the drug, chronic side-effects such as polyneuropathy and muscular atrophy have been observed. 1,4 A 21-year-old woman was diagnosed as suffering from APL in April 1998, based on M3v morphology showing hypogranular blasts with bilobulated nuclei, CD33 + CD34 + HLA-DR − immunophenotype and cytogenetic evidence of t(15;17). Complete remission was achieved after treatment with all-trans retinoic acid (ATRA) and a course of idarubicin and cytarabine within 4 weeks.…”
Section: The Editormentioning
confidence: 99%